Pengaruh Audit Tenure, Audit Opinion, Reputasi Auditor, Auditor Switching, Dan Financial Distress Terhadap Audit Report Lag - Rifzika Annafisah; Suyatmin Waskito Adi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the effect of audit tenure, audit opinion, auditor reputation, auditor switching, and financial distress on audit report lag in food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2023 period. The study employs a quantitative approach with multiple linear regression analysis using secondary data from annual reports. The results show that audit opinion, auditor reputation, and financial distress significantly influence audit report lag, while audit tenure and auditor switching do not have a significant impact. Audit opinion and auditor reputation negatively affect audit report lag, meaning companies with unqualified opinions and reputable auditors tend to complete audits faster. Conversely, financial distress has a positive effect, indicating that financially distressed firms require a longer audit process. The findings highlight the importance of financial stability and audit quality in ensuring timely financial reporting.